Prevalence and Health Care-Seeking Behavior for Childhood Diarrheal Disease in Bangladesh - Abdur Razzaque Sarker MHE, MSS; Marufa Sultana MHE, MPH; Rashidul Alam Mahumud MSc, MPH; Nurnabi Sheikh MSc, MPH; Robert Van Der Meer MSc, PhD; Alec Morton MSc, PhD (SAGE Publishing, 2016)
In Bangladesh, the burden of diarrheal diseases is significant among children <5 years old. The objective of this study is to capture the prevalence of and health care-seeking behavior for childhood diarrheal diseases (CDDs) and to identify the factors associated with CDDs at a population level in Bangladesh. We use a logistic regression approach to model careseeking based on individual characteristics. The overall diarrhea prevalence among children <5 years old was found to be 5.71%. Some factors found to significantly influence the health care-seeking pattern were age and sex of the children, nutritional score, age and education of mothers, wealth index, and access to electronic media. The health care service could be improved through working in partnership with public facilities, private health care practitioners, and community-based organizations, so that all strata of the population get equitable access in cases of childhood diarrhoea.